Use and perceived effectiveness of complementary therapies in Parkinson's disease. (January 2019) - Donley, Sarah; McGregor, Sadie; Wielinski, Catherine; Nance, Martha
Abstract: Introduction: Complementary therapies are commonly used by people with Parkinson's disease to relieve symptoms not fully addressed by pharmacologic and rehabilitation therapies currently available through medical clinics and programs. Three prior surveys in the US have shown that 40–85% of patients have used complementary therapies. We were interested in understanding what complementary therapies (CTs) our patients had used, to treat what symptoms, and whether they felt that the treatments were effective. Methods: Patients scheduled for a return visit to a center neurologist were mailed a survey and instructed to bring the completed survey to their clinic visit. The survey contained questions on CTs used, effectiveness, and for what symptoms was the CT helpful. Willingness to participate in CT research was also included in the survey. Results: 272 of 435 people with Parkinson's disease who completed the survey (62.5%) had tried some kind of CT, including a higher proportion of women than men (75.7% vs 53.8%; p < 0.01). Massage was the most frequently used therapy followed by yoga, Tai Chi, meditation and acupuncture. A high proportion of patients found the CT to be effective, for instance meditation was viewed as helpful by 85% of patients. Almost 2/3 of patients said they would be willing to participate in a research study of a CT. Conclusions: Complementary therapies are frequently used by people with Parkinson's disease coming to our center, and are viewed to be helpful for both motor and non-motor symptoms. Formal research assessments of therapies such as meditation are warranted.